Pengaruh Efikasi Diri Akademik Dan Teman Sebaya Terhadap Hasil Belajar Ekonomi : Peran Self-Regulated Learning Sebagai Variabel Mediasi - Septian Ningrum, Anisa; Rafsanjani, Mohamad Arief (Perspektif Pendidikan dan Keguruan, 2024)
The research aims to determine the influence of academic self-efficacy and peer on economic learning outcomes through self-regulated learning as a mediating variable. The type of research used is causal associative with a quantitative approach. A total of 137 students in classes X and XI of SMA Ta'miriyah Surabaya were the samples in this research. Data was obtained from the results of questionnaires and students' daily summative economic scores. The data analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS software. The research results show that directly, academic self-efficacy has a significant and positive effect on economic learning outcomes, academic self-efficacy has a significant and positive effect on self-regulated learning, self-regulated learning has a significant and positive effect on economic learning outcomes, peers have a significant and positive effect on economic learning outcomes, and peers have a significant and positive effect on self-regulated learning. Other findings show that indirectly, academic self-efficacy has a significant and positive influence on economic learning outcomes through self-regulated learning, and peers have a significant and positive influence on economic learning outcomes through self-regulated learning.